In vitro study of marginal microfiltration in indirect restorations cemented with dual cement and fluidized resins by preheating. - Cueva-Buendía, Luis Alberto (2020)
Objectives: To determine in vitro if there is a difference in the marginal microfiltration of composite resin inlays, cemented with dual resin cement and fluidized composite by preheating, evaluated with macrophotographs at the Private University of Huancayo Franklin Roosevelt 2018 - 2019. Material and Methods: In vitro experimental type, quasi-experimental design. Results: It was found that of the inlays cemented with dual resin cement and with fluidized composite resin, they presented the highest percentages: 80% and 70% respectively at the “medium level of microleakage”, in terms of “absence of microleakage”, the fluidized resin had 5% as opposed to 0% of dual cement, and the “high microleakage” level was present only in the 10% dual cement cemented inlays and both equaled 0% in “very high” grade microleakage. Noting a slight superiority in terms of the lower presence of microleakage in the inlays cemented with fluidized composite resins. Conclusions: It was determined that there is a significant difference between the marginal microleakage of mesio-occluso-distal composite resin inlays cemented with dual resin cement and cemented with composite resin fluidized by preheating, evaluated with macrophotographs. Chi square of 0.325 and a p <significance level α (0.000 <0.05).